In Vitro Evaluation of Trichoderma Species and Botanicals for the Management of Lasiodiplodia theobromae - Tapwal, Ashwani; Verma, Swedha; Thakur, Gunjan (Indian Forester, 2017)
Lasiodiplodia theobromae, the causal agent of bark canker and die-back of Dalbergia sissoo is a common and an opportunistic soil-borne pathogenic fungus, known to attack number of plant species. Potential of three Trichoderma species and phyto-extracts of ten plants to inhibit the growth of L. theobromae was evaluated under laboratory conditions. Trichoderma species have restricted the growth of L. theobromae ranging from 3.17 to 75.35 per cent in dual culture and by the release of volatile and non-volatile metabolites in the culture media. The rate of growth inhibition was increased with age of Trichoderma species in the culture media. T. viride was recorded as most effective antagonist followed by T. harzianum and T. koningii. Among botanicals, the extracts of selected plant species inhibited the growth of L. theobromae in the range of 1.25-48.05 per cent. The extracts of Azadirachta indica and Santalum album were most effective and Murraya koenigii was least effective.